LigSearch: a knowledge‐based web server to identify likely ligands for a protein target. (1st December 2013) - de Beer, Tjaart A. P.; Laskowski, Roman A.; Duban, Mark‐Eugene; Chan, A. W. Edith; Anderson, Wayne F.; Thornton, Janet M.
<x xml:space="preserve">Abstract</x> Identifying which ligands might bind to a protein before crystallization trials could provide a significant saving in time and resources. LigSearch, a web server aimed at predicting ligands that might bind to and stabilize a given protein, has been developed. Using a protein sequence and/or structure, the system searches against a variety of databases, combining available knowledge, and provides a clustered and ranked output of possible ligands. LigSearch can be accessed at http://www.ebi.ac.uk/thornton‐srv/databases/LigSearch.